A Review of Recent Research on Green Vehicle Routing Problem - Durmaz, Nida; Budak, Aysenur (IEOM Society, 2021)
In today's world, environmental sensitivity increases with the overuse of energy and the increasing pollution in parallel with this situation, consistently. In this context, Green Vehicle Routing Problem attracts the attention of researchers as it is a scientific research problem that takes awareness of environmental impact and resource efficiency into account simultaneously. This paper investigates literature related to frequently used objective functions, constraints, fleet type, number of depots, parameter uncertainty and solution techniques in GVRPs. This study covers publications between 2011 and 2021 including 72 papers. The distinctness of this paper lies in highlighting the main features of GVRP that provide the direction of the development of researches. © 2022 Elsevier B.V., All rights reserved.
4th European International Conference on Industrial Engineering and Operations Management, IEOM 2021 -- Virtual, Online -- 273059
Keywords: Environmental Considerations; Green Vehicle Routing Problem; Literature Review